Early-cleavage is a reliable predictor for embryo implantation in the GnRH agonist protocols but not in the GnRH antagonist protocols - Hwu Yuh-Ming; Yang Wen-Jui; Lee Robert; Li Sheng-Hsiang; Fleming Steven (BMC, 2009)
Abstract Background To test if early-cleavage was a strong predictor of pregnancy in patients receiving either a GnRH agonist long protocol or a GnRH antagonist protocol for in-vitro fertilization treatment (IVF) and intracytoplasmic sperm injection (ICSI). Methods This retrospective study included 534 patients undergoing a fresh cycle of oocyte retrieval and the day-3 embryo transfer (from 22 to 46 years old). Of the 534 patients treated, 331 received a GnRH agonist long stimulation protocol (GnRH agonist group) for ovarian stimulation and 203 patients received a GnRH antagonist protocol (GnRH antagonist group). In each group, patients who had at least one early-cleavage embryo transferred were designated as the 'early-cleavage' subgroup. Patients who had no early-cleavage embryos transferred were designated as the 'late-cleavage' subgroup. Results The early cleavage rate was significantly lower in the GnRH antagonist group compared with that in the GnRH agonist group (IVF cycles: 34% versus 20%; ICSI cycles: 50% versus 37.8%, respectively, P < 0.0001). In the GnRH agonist group, the pregnancy rates were significantly higher in the early-cleavage subgroup than those in the late-cleavage subgroup (53.7% vs 33.9%, P < 0.0001). In the GnRH antagonist group, the pregnancy rates were not significantly different between the early-cleavage and late-cleavage subgroups (45.9% vs 43.8%, P > 0.05). Conclusion Early cleavage of zygote is not a reliable predictor for embryo implantation potential in using the GnRH antagonist protocol. Furthermore, the implantation rates between the GnRH agonist and GnRH antagonist groups were comparable.